2010
DOI: 10.1016/j.trsl.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered mitochondrial membrane potential, mass, and morphology in the mononuclear cells of humans with type 2 diabetes

Abstract: Mitochondrial membrane hyperpolarization and morphological changes are important in inflammatory cell activation. Despite the pathophysiological relevance, no valid and reproducible method for measuring mitochondrial homeostasis in human inflammatory cells is currently available. This study's purpose was to define and validate reproducible methods for measuring relevant mitochondrial perturbations and to determine whether these methods could discern mitochondrial perturbations in type 2 diabetes mellitus (T2DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 46 publications
6
114
0
4
Order By: Relevance
“…Considerable research has demonstrated that free radical injury at the level of mitochondria severely affects neutrophil functional longevity [7]. Recently, we and others have delineated the role and clinical significance of mitochondrial dysfunction in peripheral blood lymphocytes of diabetic subjects [8,9]. In continuation to our previous investigation in the T2DM cohort, we speculate that perturbed interplay of mitochondria-nuclear cross talk may as well create an imbalance in oxidative function of neutrophils in T2DM subjects contributing to increased cellular demise.…”
Section: Introductionsupporting
confidence: 71%
“…Considerable research has demonstrated that free radical injury at the level of mitochondria severely affects neutrophil functional longevity [7]. Recently, we and others have delineated the role and clinical significance of mitochondrial dysfunction in peripheral blood lymphocytes of diabetic subjects [8,9]. In continuation to our previous investigation in the T2DM cohort, we speculate that perturbed interplay of mitochondria-nuclear cross talk may as well create an imbalance in oxidative function of neutrophils in T2DM subjects contributing to increased cellular demise.…”
Section: Introductionsupporting
confidence: 71%
“…18) Therefore, we measured the effect of AIII on ATP levels and mitochondrial mass using an ATP assay and by staining with NAO, which binds to cardiolipin (a phospholipid specifically present on the mitochondrial membranes), 19) respectively. AIII dose-dependently increased myotube NAO fluorescence intensities (Fig.…”
Section: Effect Of Aiii On Pgc1α Expression In C2c12 Myotubesmentioning
confidence: 99%
“…This is clinically important since mitochondrial dysfunction can initiate a series of cellular events that promote pro-inflammatory signaling pathways or lead to cell death. Several studies have characterized mitochondrial function of peripheral blood mononuclear cells and platelets in conditions such as fibromyalgia, diabetes, septic shock, and Alzheimer's disease [3][4][5][6][7] . For example, a recent study evaluated the bioenergetics of platelets as a marker for mitochondrial function and found that platelets from Type 2 diabetic patients had diminished mitochondrial oxygen consumption 7,8 .…”
Section: Introductionmentioning
confidence: 99%